Ketahanan Keluarga di Kecamatan Pontang Kabupaten Serang Provinsi Banten - Riny Handayani; enggar Utari; Muhammad Iman Santoso (JIPAGS (Journal of Indonesian Public Administration and Governance Studies), 2018)
Related to Family Resilience in Banten Province, especially in Serang District. Several factors (vulnerability) are high poverty and high rates, imbalances of economic development in cities and countries and high seriously indicated outflows quickly. Human Development (HDI) of 65.12 far below the provinces of 70, 96. Unemployment Rate (TPT) even recorded the highest at 14.80% with the answer the lowest TPT area in the province of Banten is the City of South Tangerang 6.13% . Pontang Sub-district is recorded as the largest enclave of Indonesian Migrant Workers (TKI) on a local and national scale that will undoubtedly affect various matters relating to family circumstances that are directly related to Family Resilience conditions. The concept of Family Resilience is examined with Input, Process and Output Components (Sunarti, 2003). Family welfare depicted from several indicators described in Input and Output Components in Pontang Sub-district shows a positive situation, with relatively optimal conditions in indicators of the Maternal, Infant and Toddler Economy, Education and Conditions. Indicators that support the optimal for children, Complete, Used Residents of Correctional Institution, Psychological Social Problem Family, Problematic Migrant Worker and Trafficking Victims. The relatively optimal condition of social welfare in Pontang Sub-district can be used as an indicator of Family Resilience in Pontang Sub-District because Family Welfare is an important part of Family Resilience. As for the Process Group described by participants in the Maternal Health Program, Infants and Toddlers still show less conditions. Family resilience indicated optimal in Pontang Sub-district can be interpreted that the family as one of the family members that can develop (potential vulnerability) that potentially cause damage (potential damage) in family life.